BAGAIMANA RENCANA MASA DEPANMU?: PENGARUH JENIS KELAMIN DAN KEPRIBADIAN TERHADAP MINAT SISWA DALAM MEMILIH JURUSAN PERGURUAN TINGGI - Dewi, Rooswita Santia; Khairina, Nadia; Rachmah, Dwi Nur; Hidayatullah, Muhammad Syarif (Universitas Tanjungpura, 2025)
Person's personality can affect what they might do in response to a particular circumstance or event. According to the study's findings, personality has an impact on a person's behavior, including their career decisions. Based on these conclusions, we want to identify the root cause by examining the impact of personality on interest in general election lectures based on gender and sex. 354 Senior High School students who were getting ready for university selection made up the study's sample. Respondents in the study This is student class XII (Science and Social Sciences) at school Senior High School (SMA) in South Kalimantan. Data were retrieved for more than 2 months and were nonparametric data. Collected data will be analyzed using analysis Chi-Square. The result shows that there wasn